Improvement of rodent pest control strategy: II - Response of wild brown rats to baits containing preservative previously exposed to unfavourable environmental conditions - Blažić, Tanja; Đurović-Pejčev, Rada; Đorđević, Tijana; Jovičić, Ivana; Međo, Irena; Stojnić, Bojan; Jokić, Goran (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
Control of brown rats (Rattus norvegicus) is an indispensable measure of protection ofhuman population and domestic animals, aimed at preventing the spread of infectiousdiseases, and a measure of protection of goods and commodities that the brown ratcan damage by its presence and activities. Rodent control procedures in environmentswith unfavourable conditions, such as high temperature and humidity, may fail due toreduced bait palatability caused by its degradation. Baits were prepared based on OEPP/EPPO recommendations, while ECHA recommendation was followed for bait exposure tounfavourable environmental conditions. Placebo baits were prepared by mixing groundmaize grain and paraffin. Test baits, made by mixing the placebo bait with sorbic acid, wereexposed to unfavourable environmental conditions (temperature 30-35 ⁰C and humidity90-95%). Brown rats previously captured from a wild population were used as the testorganism. After an acclimation period, the animals were subjected to a four-day choicefeeding test in which they were simultaneously offered placebo and test baits. The averagebait palatability was unchanged, and the palatability of bait containing the preservative was48.85 %. Furthermore, the preservative had no influence on bait consumption, comparedto baits in the pre-test period, as there was no statistical difference in total amounts of baitconsumed in the tests. The results indicate that 1% sorbic acid can be used as a potentiallygood additive to baits that are planned to be used in sewage systems and other areas whereunfavorable environmental conditions prevail and there is a risk of rapid mold developmentand bait decay.
Keywords: Rattus norvegicus; rodent; preservatives; mold; palatability